2013
DOI: 10.1517/14656566.2013.782285
|View full text |Cite
|
Sign up to set email alerts
|

Stavudine extended release (once-daily, Bristol-Myers Squibb) for the treatment of HIV/AIDS

Abstract: The development of d4T XR has only been partially successful with regard to its objectives. Improved pharmacokinetic properties allow its once daily dosing, and although it exhibits less mitochondrial toxicity it is still hampered by its development in a significant proportion of patients. This has caused its use to be almost residual in industrialised countries. As of now, d4T XR has not been made available in developing countries, despite the extended use of the immediate-release formulation. Currently, if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Likewise, the d4T containing regimen was not associated with PN, which is contrary to the findings in other studies [ 27 , 31 , 32 ], however, is similar with the study by Luma et al [ 14 ] which showed no association of d4T use with PN. A possible reason being that people who experience PN as result of d4T have it in the initial stages of the therapy [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 68%
“…Likewise, the d4T containing regimen was not associated with PN, which is contrary to the findings in other studies [ 27 , 31 , 32 ], however, is similar with the study by Luma et al [ 14 ] which showed no association of d4T use with PN. A possible reason being that people who experience PN as result of d4T have it in the initial stages of the therapy [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 68%
“…Exposure to “D drugs” including d4T has proved to be the most consistent risk factor associated with PN [ 7 , 9 , 41 , 42 ]. However, this study did not find a similar association.…”
Section: Discussionmentioning
confidence: 99%
“…Simplified strategies have been demonstrated to improve adherence and patient satisfaction in other chronic disease management schema, including cardiovascular disease, hypertension, elevated cholesterol, thrombosis, depression, and osteoporosis [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In recent decades, increasingly simplified contraception methods have brought with them higher efficacy and patient convenience [34].…”
Section: The Promise Of Drug Simplificationmentioning
confidence: 99%
“…The use of long-acting injectable glucagon-like peptide-1 receptor (GLP-1R) agonists for the treatment of diabetes has been shown to improve glycemic control, glycolated hemoglobin, promote weight loss as well as reduce cardiovascular risk by improving blood pressure control and lipid levels [45][46][47]. Injectable hormones have become the mainstay of long-acting contraception, decreasing unintended pregnancies and abortions while achieving lower failure rates in both resourced and under resourced countries [34,49,50].…”
Section: Long-acting Injectibles (Lais)mentioning
confidence: 99%